O Acesso à Informação como instrumento de participação social: uma análise do Serviço de Informação ao Cidadão na Universidade Federal do Pará (2012-2018) - ROCHA, Roseane da Vera Cruz da (2022)
The Federal Law 12.527 of November 18, 2011 was instituted to competence to guarantee rights and to modify the relations among citizens and public institutions. This is an achievement about a principle considered fundamental in the Constitution of the Federative Republic of Brazil of 1988 – CRFB/88, which is the right of access to public information. This way, this paper seeks to contextualize this right from a small historical cut in the control and access of public information from classical antiquity to contemporary context, it reveals the social role of the archives in this construction of the public dimension of information. These questions have been discussed beyond the historical focus and seek to understand the logic of the law from an analysis of Citizen Information Service of the Federal University of Pará (UFPA), is marking out the instruments of public transparency as a mechanism of control and social participation.